The Effect of Health Sector Reform on Health Services Delivery in Tanzania: A Comparative Study of Two Districts - Nhembo, Martha; Benedict, Grace; Bashemera, Domitilla (Tanzania Journal for Population studies and Development, 2011)
Adopting the public private partnership theory, this article explains the importance of involving private sector in health service delivery; and uses the horizontal theory to advocate the right of all people to access health services. Findings from a study conducted in Dodoma rural and Morogoro Municipality indicated that the number of patients served per medical officer decreased after reform, and that the number of patients served for each health facility was below the national average. Also the numbers of private health facilities, especially in urban or towns, are associated with the lowering of the number of patients in public health facilities. It was also revealed that some people have been discriminated in accessing quality health services on the basis of income, distance and location. In Morogoro Municipality, it was revealed that some people were not getting health services due to beliefs related to witchcraft and traditional healers. This situation was attributed to the uneven distribution of health facilities between the urban and peripheral areas. The study recommends that more emphasis should be on health education to the community members so as to create awareness on the importance of health services against beliefs on witchcraft and traditional healers in Morogoro Municipality. Moreover, the government should increase trained health staff in Dodoma Rural District.